Influence of Calcification Solution on in vitro Chitosan Mineralization - Beppu,Marisa M. (2002)
The influence of the calcification solution on the mineralization of chitosan membranes was analysed. Two factors were studied: pH and chemical composition (excess of calcium or phosphate ions) of solutions. Substrates (membranes) of chitosan underwent mineralization by soaking in calcification solutions for 7 days at 36.5 °C. As expected, SEM-EDS analyses demonstrated that higher pH and concentration of ions increases deposition, however, the morphology and composition of these deposits varies depending on which ion (phosphate or calcium) is in excess. Larger spherical deposits are observed when a calcium-rich solution is used instead of a phosphate-rich one. In the latter, the interconnectivity of the inorganic and organic (matrix) phases is very different, suggesting a different mechanism of deposition for each situation.